Measurement of MHD Turbulence Properties by Synchrotron Radiation Techniques - Zhang, Jian-Fu; Wang, Ru-Yue (Frontiers in Astronomy and Space Sciences, 2022)
It is well-known that magnetohydrodynamic (MHD) turbulence is ubiquitous {\it in astrophysical environments}. The correct understanding of the fundamental properties of MHD turbulence is a prerequisite for revealing many key astrophysical processes. The development of observation-based measurement techniques has significantly promoted MHD turbulence theory and its implications in astrophysics. After describing the modern understanding of MHD turbulence based on theoretical analysis {\it and direct numerical simulations, we review recent developments related to synchrotron fluctuation techniques.} Specifically, we comment on the validation of synchrotron fluctuation techniques and the measurement performance of several properties of magnetic turbulence based on data cubes from MHD turbulence simulations and observations. Furthermore, {\it \textbf{we propose to strengthen the studies of the magnetization and 3D magnetic field structure's measurements of interstellar turbulence. At the same time, we also discuss the prospects of new techniques for measuring magnetic field properties and understanding astrophysical processes, using a large number of data cubes from the Low-Frequency Array (LOFAR) and the Square Kilometre Array (SKA).